High-altitude-resolution observation of the upper stratosphere and lower mesosphere using Jicamarca VHF radar - Fukao, S. (1991)
The high-power VHF radar technique is a powerful tool to lnvestigate winds and turbulence in the middle atmosphere. However, an entire wind or power profile from the upper troposphere to the lower thermosphere. (10-100 km) has not yet been obtained.- Especially, it is very difficult to observe the so-called ''gap region" from 35 to 60 km due to weak echo power. Recently, the Jicamarca VHF radar facility (50 MHz) in Peru has been greatly improved, and a height resolution of 250-500 m is now achieved by pulse compression using 16- or 32-bit complementary codes. This paper presents a preliminary result of Jicamarca radar observations of the upper stratosphere and lower mesosphere, including the "gap region'', conducted on Sept. 24-28, 1990.